John Haywood, A Manual of the Laws of North-Carolina, Arranged under Distinct Heads in Alphabetical Order, Oaths and Affirmations 40 (1814) - (:unkn) unknown (My University, 1814)
The oath of a Constable, § XXIII: You shall swear that you will well and truly serve the State of North Carolina in the office of a constable, you shall see and cause the peace of the State to be well and duly preserved and kept according to your power, you shall arrest all such persons as in your sight shall right or go armed offensively, or shall commit or make any riot, affray or other breach of the peace; you shall do your best endeavor, upon complaint to you made, to apprehend all felons, and rioters, or persons riotously assembled; and if any such offender shall make resistance with force, you shall make hue and cry, and shall pursue them according to law
Keywords: GOING ARMED